2002
DOI: 10.1002/1521-3773(20020402)41:7<1178::aid-anie1178>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Selective Direct Synthesis of Organofunctionalized Dialkylgermanes from Solvochemically Activated Germanium

Abstract: Kinetic inertness overcome: The selective coupling of Ge−E bonds (E=halogen, C) can be achieved at 130°C by direct synthesis from activated germanium. Alkyl bromides with an additional carbonyl function (see scheme) can be converted in a controlled manner into dibromodiorganogermanes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 23 publications
1
5
0
1
Order By: Relevance
“…A thermoanalytical investigation of the orange-colored amorphous substance brings further support to the idea of (at least partial) medium range order in this material. As we already reported in previous work [23], the amorphous product shows two distinct peaks in the differential thermal analysis, an exothermal wave for cold crystallization around 490°C and an endothermal signal for melting around 909°C. Calorimetric measurements revealed that the enthalpy of cold crystallization (9.0 kJ/mol) is only about 30 % of the melting enthalpy (31.8 kJ/mol) of germanium.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…A thermoanalytical investigation of the orange-colored amorphous substance brings further support to the idea of (at least partial) medium range order in this material. As we already reported in previous work [23], the amorphous product shows two distinct peaks in the differential thermal analysis, an exothermal wave for cold crystallization around 490°C and an endothermal signal for melting around 909°C. Calorimetric measurements revealed that the enthalpy of cold crystallization (9.0 kJ/mol) is only about 30 % of the melting enthalpy (31.8 kJ/mol) of germanium.…”
Section: Resultssupporting
confidence: 77%
“…For comparison with the nanoscale product, bulk amorphous hydrogenated germanium [23] was synthesized from GeCl 4 with an excess of Li[Et 3 BH] in toluene at 100°C. In contrast to the synthetic route reported previously [23], this synthesis does not require the rather expensive GeCl 2 ·dioxane as a starting material and yields a product that is free of dioxane containing impurities [24].…”
Section: Resultsmentioning
confidence: 99%
“…[ 25 ] Additionally, by means of direct synthesis, it is possible to obtain dialkylgermanes from germanium, which can be used as precursors for photoconducting polymers and photoresists. [ 26 ] Moreover, direct synthesis is widely used for obtaining classical commercial reagents. For example, there is a well‐known reaction of magnesium with alkyl and aryl halides in ether to produce the Grignard reagents.…”
Section: Introductionmentioning
confidence: 99%
“…Ein weiterer, in zukünftigen Arbeiten zu klärender Aspekt ist die Ähnlichkeit der Farbe von GeBr zu der des von Schlecht kürzlich vorgestellten aktivierten Germaniums, welches auf einer vollkommen anderen Syntheseroute erhalten wurde[14].Die Versuchsdurchführung erfolgt in der in Abbildung 2 angegebenen Anlage, welche über eine Öldiffusionspumpe (Balzers Diff 900) auf einen Druck von 5·10 Ϫ6 mbar evakuiert wird. Der im Zentrum der Anlage befindliche Graphitreaktor, in dem Germanium vorgelegt wurde, wird induktiv über ein hochfrequentes Wechselfeld von 1000 kHz auf 1550°C erhitzt, wobei die Ofentemperatur im unteren Drittel des Ofens mit einem Strahlungspyrometer gemessen wird (Hutter&Klüger GmbH & Co KG, Quotientenpyrometer PYROS 108).…”
unclassified